Increased expression of ER stress, inflammasome activation, and mitochondrial biogenesis-related genes in peripheral blood mononuclear cells in major depressive disorder - Munshi, Soumyabrata; Alarbi, Ahlam M.; Zheng, Haixia; Kuplicki, Rayus; Burrows, Kaiping; Figueroa-Hall, Leandra K.; Victor, Teresa A.; Aupperle, Robin L.; Khalsa, Sahib S.; Paulus, Martin P.; Teague, T. Kent; Savitz, Jonathan (Molecular psychiatry, 2025)
A subset of major depressive disorder (MDD) is characterized by immune system dysfunction, but the intracellular origin of these immune changes remains unclear. Here we tested the hypothesis that abnormalities in endoplasmic reticulum (ER) stress, inflammasome activity and mitochondrial biogenesis contribute to the development of systemic inflammation in MDD. RT-qPCR was used to measure mRNA expression of key organellar genes from peripheral blood mononuclear cells (PBMCs) isolated from 186 MDD and 67 healthy control (HC) subjects. The comparative C T (2 -ΔΔCT ) method was applied to quantify mRNA expression using GAPDH as the reference gene. After controlling for age, sex, BMI, and medication status using linear regression models, expression of the inflammasome ( NLRC4 and NLRP3 ) and the ER stress ( XBP1u, XBP1s , and ATF4 ) genes was found to be significantly increased in the MDD versus the HC group. Sensitivity analyses excluding covariates yielded similar results. After excluding outliers, expression of the inflammasome genes was no longer statistically significant but expression of the ER stress genes ( XBP1u, XBP1s , and ATF4 ) remained significant and the mitochondrial biogenesis gene, MFN2 , was significantly increased in the MDD group. NLRC4 and MFN2 were positively correlated with serum C-reactive protein concentrations, while ASC trended significant. The altered expression of inflammasome activation, ER stress, and mitochondrial biogenesis pathway components suggest that dysfunction of these organelles may play a role in the pathogenesis of MDD.